2022
DOI: 10.3389/fnut.2022.1004084
|View full text |Cite
|
Sign up to set email alerts
|

A postbiotic fermented oat gruel may have a beneficial effect on the colonic mucosal barrier in patients with irritable bowel syndrome

Abstract: BackgroundImpaired intestinal permeability and microbial dysbiosis are important pathophysiological mechanisms underlying irritable bowel syndrome (IBS). ReFerm®, also called Profermin®, is a postbiotic product of oat gruel fermented with Lactobacillus plantarum 299v. In this study, we investigated whether ReFerm® has a beneficial effect on the intestinal epithelial barrier function in patients with IBS.Materials and methodsThirty patients with moderate to severe IBS-diarrhoea (IBS-D) or IBS-mixed (IBS-M) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…Full-text screening was conducted in the remaining 150 articles. We identified 46 studies of probiotic therapy in IBS [16–59], three studies of prebiotics [60–62] and three studies of synbiotics [63–65]. Finally, 50 articles reporting 52 studies were included in this meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Full-text screening was conducted in the remaining 150 articles. We identified 46 studies of probiotic therapy in IBS [16–59], three studies of prebiotics [60–62] and three studies of synbiotics [63–65]. Finally, 50 articles reporting 52 studies were included in this meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Although the synbiotics did not significantly increase the response rate in IBS patients ( P >0.05), it could reduce flatulence to some extent ( P =0.038). Bednarska et al using synbiotics (a postbiotic fermented oat gruel with probiotics) found there was no significant difference of response rate between intervention group (5/18) and control group (4/12) [65].…”
Section: Resultsmentioning
confidence: 99%
“…Male rats aged 8–12 weeks were included in the study. It has been reported that patients with IBS exhibit increased intestinal permeability 33 . In this study, an IBS model was created by subjecting rats to WAS 34 .…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that patients with IBS exhibit increased intestinal permeability. 33 In this study, an IBS model was created by subjecting rats to WAS. 34 The rats were randomly divided into three groups: the control group, the model group, and the lidocaine group, with seven rats in each group.…”
Section: Construction Of the Experimental Modelmentioning
confidence: 99%
“…The authors, therefore, concluded that supplementation with Lactobacillus plantarum 299v did not show significant efficacy in the treatment of IBS [ 64 ]. In contrast, a randomized experimental study also conducted in 2022 by Bednarska et al noted that Lactobacillus plantarum 299v had a more beneficial effect on the course of IBS compared to placebo [ 65 ]. In this analysis, 30 people diagnosed with moderate IBS were assigned to one of two groups.…”
Section: Supplementationmentioning
confidence: 99%